Railway Agency, The Symbol of Dependable Service
Present day convenience and dependability of the nation's Railway Express service for meeting the shipping needs of the American family are typified in this scene, one of the series of seven striking oil painting by Robert E. Lee, exhibited at the booth of the Railway Express Agency in the Travel and Transport Building on the A Century of Progress Exposition grounds.